2010
DOI: 10.1007/s10096-010-1097-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and virulence of the present hantaviruses in Bosnia and Herzegovina: the impact on renal function

Abstract: SummaryDobrava (DOBV) and Puumala (PUUV) viruses are endemic throughout the Balkans and cause high fever with renal syndrome (HFRS). The aim was to assess impact of two different HTV on renal function in HFRS patients during acute stage of illness. We also aimed to assess DOBV and PUUV distribution between symptomatic, HFRS patients and asymptomatic hantavirus antibody positive subjects. The study included 264 symptomatic, HFRS patients and 63 asymptomatic hantavirus antibody positive healthy subjects. In our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The more severe clinical picture of infection with DOBV compared to PUUV corresponds to the observations made in other studies that compared infections with PUUV and different DOBV genotypes. Patients with DOBV infections were more often hypotensive, exhibited higher levels of serum creatinine, displayed more severe thrombocytopenia and required dialysis more often compared to patients infected with PUUV [3436]. Our analysis of the clinical course of the two infections revealed further differences between the two infections.…”
Section: Discussionmentioning
confidence: 68%
“…The more severe clinical picture of infection with DOBV compared to PUUV corresponds to the observations made in other studies that compared infections with PUUV and different DOBV genotypes. Patients with DOBV infections were more often hypotensive, exhibited higher levels of serum creatinine, displayed more severe thrombocytopenia and required dialysis more often compared to patients infected with PUUV [3436]. Our analysis of the clinical course of the two infections revealed further differences between the two infections.…”
Section: Discussionmentioning
confidence: 68%
“…Recent study of clinically manifested hantavirus infections in Bulgaria revealed that infections in 16/23 (69.6%) patients with HFRS recognized for 2 years, 2013‐2014, were caused by DOBV while PUUV was shown as prevalent in Slovenia, Croatia, Bosnia, and Herzegovina . Initial investigation of Bulgarian patients with HFRS revealed only DOBV‐specific sequences .…”
Section: Discussionmentioning
confidence: 99%
“…Dialysis treatment is needed in 0%-6% of PUUVinfection-induced acute renal failure [73,93,97]. In DOBV infection, the corresponding figures have been 16%-48% [47,97].…”
Section: Clinical Picturementioning
confidence: 99%